NOTICING PRAGMATIC DIFFERENCES BETWEEN L1 AND L2 COMMUNICATION (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This paper reviews the literature on similarities and differences between first. and second language lexical acquisition. After a brief discussion of differences in input, we go on to early lexical development, considering both the speed of acquisition as well as possible reasons for more efficient lexical learning in first language acquisition as compared to second language acquisition